2021
DOI: 10.3390/environments8110117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and Adapting Climate Change Impacts on Rice Production in Indonesia: A Case Study of the Keduang Subwatershed, Central Java

Abstract: Predicting the effect of climate change on rice yield is crucial as global food demand rapidly increases with the human population. This study combined simulated daily weather data (MarkSim) and the CERES-Rice crop model from the Decision Support System for Agrotechnology Transfer (DSSAT) software to predict rice production for three planting seasons under four climate change scenarios (RCPs 2.6, 4.5, 6.0, and 8.5) for the years 2021 to 2050 in the Keduang subwatershed, Wonogiri Regency, Central Java, Indonesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…It carries out research incubation and development activities, product commercialization, and integration of agriculture, animal husbandry, energy, and natural resources into a sustainable Science Techno Park. Some of their published studies focused on drought-tolerant rice cultivars (Salsinha et al, 2020(Salsinha et al, , 2021Trijatmiko et al, 2014), farmers' technical efficiency (Mulyani et al, 2020;Widyantari et al, 2018Widyantari et al, , 2019, systems of rice intensification (Arif et al, 2015;Syahrawati et al, 2018), and climate change adaptation (Ansari et al, 2021).…”
Section: Institutionsmentioning
confidence: 99%
“…It carries out research incubation and development activities, product commercialization, and integration of agriculture, animal husbandry, energy, and natural resources into a sustainable Science Techno Park. Some of their published studies focused on drought-tolerant rice cultivars (Salsinha et al, 2020(Salsinha et al, , 2021Trijatmiko et al, 2014), farmers' technical efficiency (Mulyani et al, 2020;Widyantari et al, 2018Widyantari et al, , 2019, systems of rice intensification (Arif et al, 2015;Syahrawati et al, 2018), and climate change adaptation (Ansari et al, 2021).…”
Section: Institutionsmentioning
confidence: 99%
“…In the same year, Erni Susanti et. all [25] evaluated the projections of rice productivity in mainland Java with two other studies were conducted in the Keduang Subwatershed, Central Java [26] and West Nusa Tenggara [27]. By 2022, at the time of this review is authored, the only research on land suitability analysis for rice farming that uses RCP4.5 scenario is conducted in Sukabumi District to assess the effect of climate changes projected between 2020 [28].…”
Section: Climate Change Scenariomentioning
confidence: 99%
“…The use of GCM in Indonesia in this case is highly variative, for instance a study conducted by A. Candradijaya, et. all [17] and Andrianto Ansari, et.all [26] have used up to 17 GCM. The 17 GCM used by A. Chandradijaya, et.…”
Section: Number Of Publicationmentioning
confidence: 99%
“…Therefore, this circumstance challenges Indonesian food security and could affect socioeconomic aspects of the country since the agriculture sector has a significant contribution to employment and the economy [11]. Plenty of studies confirmed the negative impact of climate change on paddy yield or production [12][13][14][15][16].To the best of our knowledge, studies assessing the impact of climate change on wetland paddy yield nationwide in the Indonesian context are still limited. Many of them only assessed the impacts on the regional level such as [14] for Bali Province, [16] for a subdistrict in Central Java Province and [11] for West Nusa Tenggara Province.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of studies confirmed the negative impact of climate change on paddy yield or production [12][13][14][15][16].To the best of our knowledge, studies assessing the impact of climate change on wetland paddy yield nationwide in the Indonesian context are still limited. Many of them only assessed the impacts on the regional level such as [14] for Bali Province, [16] for a subdistrict in Central Java Province and [11] for West Nusa Tenggara Province. Our study aims to enrich literature and empirical works on the impact of climate change variables on wetland paddy yield in the nationwide context of Indonesia.…”
Section: Introductionmentioning
confidence: 99%